2020
DOI: 10.1155/2020/9761406
|View full text |Cite
|
Sign up to set email alerts
|

A First Step to a Biomarker of Curative Surgery in Colorectal Cancer by Liquid Biopsy of Methylated Septin 9 Gene

Abstract: Objectives. To confirm that patients affected by colorectal cancer have the V2 region of Septin 9 (SEPT9) gene hypermethylated in the circulating free DNA from a peripheral blood sample before surgery and to determine if this hypermethylated DNA disappears from the patients after complete resection of the tumour. Methods. Plasma from 10 patients with colorectal cancer was collected preoperative and three months after surgery. The analysis of the methylation status of the promoter region of the SEPT9 gene was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Hypermethylated SEPT9 ctDNA disappears after 3 months following surgery, suggesting that this molecule may be the first non-invasive biomarker for postsurgical follow-up [ 82 , 83 ]. The plasma-based SEPT9 gene methylation assay is currently an FDA-approved non-invasive CRC screening test known as Epi proColon ® 1.0 [ 79 , 84 ].…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…Hypermethylated SEPT9 ctDNA disappears after 3 months following surgery, suggesting that this molecule may be the first non-invasive biomarker for postsurgical follow-up [ 82 , 83 ]. The plasma-based SEPT9 gene methylation assay is currently an FDA-approved non-invasive CRC screening test known as Epi proColon ® 1.0 [ 79 , 84 ].…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…The COLVERA ® (Clinical Genomics, Bridgewater, NJ, USA) assay is a 2-gene ( BCAT1 / IKZF1 ) methylation-specific, plasma ctDNA platform that is also commercially available and has shown greater sensitivity for recurrence in resected, localized CRC than CEA [ 28 , 40 , 41 , 42 , 43 ]. Among the earlier genes whose methylation in ctDNA has been described in CRC includes SEPT9 , for which several groups have shown that postoperative ctDNA-positivity for SEPT9 carries high specificity for predicting recurrent CRC [ 44 , 45 , 46 , 47 , 48 ] while conferring a median lead time of 8 months prior to radiographic detection of recurrence in resected CRC patients [ 27 ].…”
Section: Detection Of Minimal Residual Disease and Recurrences In Resected Stage I–iii Colorectal Cancermentioning
confidence: 99%
“…Studies have shown that the rate of SEPT9 methylation in peripheral blood of patients with CRC is related to clinicopathological features; for example, SEPT9 methylation is positively correlated with the malignancy of CRC [11][12][13]. After radical resection of colorectal cancer, the level of mSEPT9 in peripheral blood decreases; however, the level increases after recurrence, suggesting that mSEPT9 in peripheral blood can be used for evaluating the pathological stages of CRC and may represent a molecular biological indicator for evaluating prognosis, recurrence, and metastasis [14,15]. However, the reported sensitivity and specificity values of plasma mSEPT9 are highly variable across studies, with the sensitivity ranging from 50.9-93.1% and specificity ranging from 62.2-93.8% [16,17].…”
Section: Introductionmentioning
confidence: 99%